The influence of socio economic status on antenatal mothers' knowledge on their rights and preferences for intra partum care - S. Zalrarah; M.H. Mohamed Hashim; A. Mazlan; T Winn (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
A cross-sectional study was carried out on 340 Malays antenatal mothers. The objectives were firstly, to determine patients' knowledge on their rights and their preferences for intra partum care. Secondly, to determine the association between selected socio economic variables (education level, occupation and monthly household income) and patients' knowledge on their rights. Lastly, to evaluate the association between selected socio economic variables and their preferences for intra partum care. Antenatal mothers with previous delivery experience in hospital were recruited from those who attended Women and Child Health Clinics in Kota Bharu district. Data were obtained, using systematic random sampling method from November 2003 to Februaty 2004. The piloted and validated questionnaire consisted of 18 questions, with six questions from each domain (socio economic, knowledge and preference) was used as the measurement tool. A trained interviewer with the purpose to increase the inter-rater reliablity of the questionnaire administered that questionnaire. Results showed the mean household income was RM1260.00 per month, 68.0% were housewives and 20.0% of respondents studied had tertiaty education. On average, only 22.0% of respondents knew their rights by responding to each knowledge domain. Majority of them prefer the delivery to be conducted by female (86.0%) and Muslim doctors (77.0%). Out of the respondents, 78.0% allowed medical and nurse trainees to assist during the delivery but only 10.0% gave more rooms for the trainees to deliver their babies. Surprisingly, only 43.0% of the mothers need pain relief probably influenced by cultural values. Furthermore, 40.0% preferred to be in labor without the presence of their husbands. Statistical analysis was performed by using SPSS Version 11.0 and findings showed there were significant associations